Green Public Procurement: A Neglected Tool in the European Green Deal Toolbox? - André Sapir; Tom Schraepen; Simone Tagliapietra (Intereconomics, 2022)
Public procurement amounts to around 14% of European Union GDP and, given this size, could well represent an important tool to foster the green transition. However, green public procurement continues to be underutilised in Europe, as several barriers to its application persist. A new EU regulatory action in this field could unlock the potential of green public procurement and add an important element to the European Green Deal toolbox.
Keywords: H57; Q58; O52; 330